Permainan Rosthik untuk Meningkatkan Hasil Belajar Gerak Dasar Siswa Sekolah Dasar - Nuryanto, Hari (SCAD Independent, 2025)
The material basic motion of the catch and throw is the material that must be studied by the fourth grade students. How ever, in the physical education learning process it is often not in accordance with the characteristics of students. In addition, learning is still monotonous and boring so that student learning outcomes are less than optional so it takes teacher creativity that involves students to create of modify learning aids. In this learning innovation making a learning aid for the game of throw and catch. The subject of this innovation work is in fourth grade SDN 4 Jrakah, totalling 19 students in the 2019/2020 school year. The data collection technique used in this learning innovation is to observe using an observation sheet instrument. From the data obtained, there was an in crease in learning outcomes as indicated by the number of students who obtained scores above the minimum completeness criteria (KKM 70). In the initial condition, only 3 students or 16% of student scored above the kkm. Score become 17 students or 89%. The conclution of this learning innovation is that the rosthik game can improve the learning outcames of the basic motion of throwing and catching in SDN 4 jrakah students. In addition, cooperation, motivation, discipline in teaching and learning activities are increased.